A new species of Splendeuptychia from the Magdalena Valley in Colombia (Lepidoptera: Nymphalidae: Satyrinae) - Huertas, Blanca; M., Cristóbal Ríos; Le Crom, Jean François (Zootaxa, 2009)
A new butterfly species Splendeuptychia ackeryi n. sp., is described from dry habitats in the Magdalena valley of Colombia. It most closely resembles the Ecuadorian east slope endemic S. toynei Willmott & Hall, 1995. Aspects of the morphology, ecology, distribution and conservation of the new species are discussed.